Producción del Tema "Donde Las Raíces Se Conectan" Proyecto de la Banda "Hologramas" - Troya Acosta, Jefferson Adrian (2013)
The culmination of the academic process gives emphasis to apply everything learned to the practice, because perform a musical production requires not only to know the theory or micking, editing and mixing, techniques. The ninety-nine percent of all songs, albums and audiovisual production depends on the judgment and excellent ear training. Talent is an essential requirement for get a high quality production, in the case of this project was necessary a thorough investigation and became a fan of “Metalcore”. Because this musical genre does not have a long time in the music industry and techniques production are not fully defined, was an advantage for this project, leading to perform different techniques and methods in the micking techniques, mixing and mastering. This can become a reference and personal signature of the producer. The objectives, personal and academic were successfully achieved, since the advance, recording and progress in the musical production in the country of Metalcore genre, showing all the technical knowledge acquired in the academic process….